Insights into aphid prey consumption by ladybirds: Optimising field sampling methods and primer design for high throughput sequencing. - Lolita Ammann; Rosemary Moorhouse-Gann; Jordan Cuff; Colette Bertrand; Laia Mestre; Nicolás Pérez Hidalgo; Amy Ellison; Felix Herzog; Martin H Entling; Matthias Albrecht; William O C Symondson (PLoS ONE, 2020)
Elucidating the diets of insect predators is important in basic and applied ecology, such as for improving the effectiveness of conservation biological control measures to promote natural enemies of crop pests. Here, we investigated the aphid diet of two common aphid predators in Central European agroecosystems, the native Coccinella septempunctata (Linnaeus) and the invasive Harmonia axyridis (Pallas; Coleoptera: Coccinellidae) by means of high throughput sequencing (HTS). For acquiring insights into diets of mobile flying insects at landscape scale minimizing trapping bias is important, which imposes methodological challenges for HTS. We therefore assessed the suitability of three field sampling methods (sticky traps, pan traps and hand-collection) as well as new aphid primers for identifying aphid prey consumption by coccinellids through HTS. The new aphid primers facilitate identification to species level in 75% of the European aphid genera investigated. Aphid primer specificity was high in silico and in vitro but low in environmental samples with the methods used, although this could be improved in future studies. For insect trapping we conclude that sticky traps are a suitable method in terms of minimizing sampling bias, contamination risk and trapping success, but compromise on DNA-recovery rate. The aphid diets of both field-captured ladybird species were dominated by Microlophium carnosum, the common nettle aphid. Another common prey was Sitobion avenae (cereal aphid), which got more often detected in C. septempunctata compared to H. axyridis. Around one third of the recovered aphid taxa were common crop pests. We conclude that sampling methodologies need constant revision but that our improved aphid primers offer currently one of the best solutions for broad screenings of coccinellid predation on aphids.